Evaluation of vector mediated gene therapy as a novel approach to mitigate cardiovascular diseases; A short review - Saleh Muhammad Raqib; Syaefudin Ali Akhmad (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2019)
Positioning in the top list of mortality and morbidity, cardiovascular disease (CVD) is required new approaches to mitigate the risk and prevalence. Recombinant DNA (rDNA) technology and genome sequencing explore the new horizon to treat CVD through modified therapy. Gene transfer mechanism eventually angiogenic gene therapy provides efficacy in early-stage heart failure. Targeted gene delivery system depicts the novel therapeutic pattern for both genetic disorder and pathophysiological deficit and opens the pathway of early diagnose and treatment. Despite  some limitations of a specific vector (viral vector) mediated gene transfer, these new approaches make  hope on CVD treatment rather than the surgery and other ways.  Furthermore, some vectors are less hazardous than viral vectors to suggest successful non-viral gene modulations to Cardiovascular tissues and perform in the clinical trial. However, plasmid-mediated gene transfer method along with genome editing technology might be the best possible approach for future CVD prognostics and diagnostics.